2021
DOI: 10.1111/jdv.17826
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal carcinoma in severe recessive dystrophic epidermolysis bullosa—an underestimated complication?

Abstract: 2 H€ usken AC, Tsianakas A, Hensen P et al. Comparison of pegylated interferon a-2b plus psoralen PUVA versus standard interferon a-2a plus PUVA in patients with cutaneous T-cell lymphoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 8 publications
(22 reference statements)
0
6
0
1
Order By: Relevance
“…1c ). One year after cemiplimab initiation, oesophageal SCC with lymph node metastases was diagnosed ( 17 ). Collagen VII is expressed in mucous membranes making them prone to trauma and squamous cell carcinoma formation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1c ). One year after cemiplimab initiation, oesophageal SCC with lymph node metastases was diagnosed ( 17 ). Collagen VII is expressed in mucous membranes making them prone to trauma and squamous cell carcinoma formation.…”
Section: Resultsmentioning
confidence: 99%
“…Collagen VII is expressed in mucous membranes making them prone to trauma and squamous cell carcinoma formation. This tumour responded well to radiotherapy ( 17 ), but the patient succumbed 1 year later at the age of 42 years due to complications including mucositis, scarring, and recurrence of the oesophageal tumour. At the last visit, the cSCC was stable and he had no metastasis.…”
Section: Resultsmentioning
confidence: 99%
“…Malignant tumors in these regions are highly invasive, often requiring tissue reconstruction, making surgical treatment less feasible than for malignant tumors developing in the skin of the extremities and trunk. In previous reports, surgical intervention was performed only in one patient (Martinez et al, 1992), with the remaining patients opting for non-surgical approaches involving radiotherapy and immunotherapy due to skin fragility and multiple comorbidities (Schwieger-Briel et al, 2022). Currently, survival of patients with DEB is often determined by SCC of skin origin (Robertson et al, 2021).…”
Section: Case Reportmentioning
confidence: 99%
“…One of the main complications of severe RDEB is development of SCC along with chronic wounds, strictures and carcinomas of the esophagus, anemia and musculoskeletal deformities. [1][2][3] According to Montaudié et al, the mean age of diagnosis of SCC in patients with RDEB is 36 years. 4 The National EB Registry in the United States reported that by the age of 35 this risk is 67.8% and reaches 90.1% at age 55.…”
Section: Dear Editorsmentioning
confidence: 99%